Numerical investigation of thermal efficiency of solar air heater at different flow rates - Alic, Erdem; Das, Mehmet; Akpinar, Ebru Kayak (Gazi Univ, Fac Engineering Architecture, 2023)
The rapid development of technologies using renewable energy sources is paving the way for new solutions to meet the increasing energy and power needs of the industry. This study investigated the thermal and flow properties of a solar air heater used in food drying in the industry. The optimum efficiency of the solar air heater (SAH) was investigated for two different absorber plate lengths (1400 mm and 1820 mm). The energy and exergy efficiency values of both collectors were compared. ANSYS FLUENT 18.1 was used as a computational fluid dynamics (CFD) numerical analysis program in the study. Analyzes were performed at three different mass flow rates as 0.038-0.054-0.070 kg/s and 3-dimension (3D), respectively. For the accuracy of the CFD analysis, the experimental results with a mass flow rate of 0.038 kg/s were compared with the analysis results. Friction coefficients were calculated from the pressure drop obtained from the analysis. Temperature, velocity, and pressure distribution variations were shown for different times of the day. The highest thermal efficiency was realized at 13:00 at a mass flow rate of 85% and 0.070 kg/s. The thermal efficiency of the collector has increased with higher flow rates. Although the increase in the mass flow through the collector decreased the outlet temperature, the valuable energy amount increased. This study demonstrated that different mass flow rates and absorber plate size significantly affect the thermal efficiency of SAH.
Havalı güneş kolektörünün farklı akış debilerinde ısıl verim değerlerinin sayısal araştırılması
Keywords: Exergy efficiency; solar energy; cfd; solar air heater; friction factor